The Policy of Cooperative and Small and Medium Enterprises Office in Improving Cooperative Achievement in Lampung Province - Fenny Andriani; Eka Deviani; Marlia Eka Putri AT (Administrative and Environmental Law Review, 2021)
Outstanding Cooperatives are cooperatives that have achievements in obtaining their performance in terms of organizational aspects, management, management aspects, productivity aspects, and benefit and impact aspects of cooperatives that are stipulated by the Decree of the State Minister for Cooperatives and Small and Medium Enterprises. The State Ministry for Cooperatives and Small and Medium Enterprises (Kementerian Koperasi dan Usaha Kecil Menengah) has launched a cooperative achievement assessment program to develop and make existing cooperatives a success. The prediction of cooperative achievements is expected to motivate existing cooperatives to function as economic institutions capable of improving the welfare of members in particular and society in general and building a national economic order that creates a developed, just. A prosperous society based on Pancasila and the 1945 Constitution. Building a national economic order creates a developed, just, and prosperous society based on Pancasila and the 1945 Constitution.